Destination Brand Storytelling Strategy: Narrative Analysis of the @dewitinalah Tourism Village Instagram Account in Kulon Progo Regency - Maryami Maryami; Hifni Alifahmi (Eastasouth Institute, 2026)
The development of social media has changed the communication strategy of tourist destinations, from an informative promotional approach to a digital narrative that builds the meaning and identity of the destination. Instagram no longer functions solely as a visual promotional medium, but rather as a digital storytelling space that shapes tourist perceptions and experiences. This study aims to analyze the Destination Brand Storytelling strategy of Tinalah Tourism Village through the Instagram content of @dewitinalah and examine the agreement in building Destination Branding based on nature, culture, and history. This study uses a qualitative approach with a narrative analysis method. The object of the study is the Instagram content of @dewitinalah for the period 2024–2025 which includes six selected posts based on thematic purposive sampling, namely the themes of nature, culture, and history. The research data is strengthened through semi-structured interviews with two key informants, namely the Manager of Tinalah Tourism Village and the Admin of Instagram @dewitinalah. The framework analysis integrates Walter Fisher's Narrative Paradigm through the concepts of Narrative Coherence and Narrative Fidelity, Zimand-Sheiner's Four Dimensions of Brand Storytelling, and Balakrishnan's Destination Branding strategy. The results of this study indicate that the Instagram content of @dewitinalah creates a relatively coherent digital storytelling that aligns with socio-cultural realities and practices of village tourism management. The themes of nature and culture display strong narrative consistency, while the historical theme enriches the destination's identity through historical dimensions and collective memory. The digital storytelling not only supports destination promotion but also plays a strategic role in shaping the image and identity of Tinalah Tourism Village. This study concludes that Destination Brand Storytelling through Instagram is an effective communication strategy for developing community-based village tourism and contributes to strengthening the identity and passion of the destination brand.